Digital Immortality - Bell, Gordon; Gray, Jim (Association for Computing Machinery, Inc., 2000)
Digital immortality, like ordinary immortality, is a continuum from enduring fame at one end to endless experience and learning at the other, stopping just short of endless life . Preserving and transmitting your ideas is one-way immortality : allowing communication with the future. Endless experience and leaning is two-way immortality : allowing “you,” or at least part of you, to communicate with the future in the sense that artifact continues to learn and evolve. Current technology can extend corporal life for a few decades. Both one-way and two-way immortality require part of a person to be converted to information ( Cyberized ), and stored in a more durable media. We believe that two-way immortality where one’s experiences are digitally preserved, and which then take on a life of their own will be possible within the this century.